2016
DOI: 10.1007/s10439-016-1634-2
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Ultrasonic Imaging of Dento-Periodontal Tissues Using a Multi-Element Phased Array System

Abstract: Intraoral ultrasonography uses high-frequency mechanical waves to study dento-periodontium. Besides the advantages of portability and cost-effectiveness, ultrasound technique has no ionizing radiation. Previous studies employed a single transducer or an array of transducer elements, and focused on enamel thickness and distance measurement. This study used a phased array system with a 128-element array transducer to image dento-periodontal tissues. We studied two porcine lower incisors from a 6-month-old piglet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Ultrasonography has great potential to become a noninvasive diagnostic imaging tool for quantitative assessment of the periodontal structures and better delivery of oral care. [19] Ultrasound has significant potential to aid surgeons in "visualizing" oral structures during minimally invasive surgery and guide local anesthesia for difficult cases [15] due to the fact that it is a real time imaging examination.…”
Section: Conclusion About 2d Periodontal Ultrasonographymentioning
confidence: 99%
“…Ultrasonography has great potential to become a noninvasive diagnostic imaging tool for quantitative assessment of the periodontal structures and better delivery of oral care. [19] Ultrasound has significant potential to aid surgeons in "visualizing" oral structures during minimally invasive surgery and guide local anesthesia for difficult cases [15] due to the fact that it is a real time imaging examination.…”
Section: Conclusion About 2d Periodontal Ultrasonographymentioning
confidence: 99%
“…An early study reported unfavourable results, suffering from low image resolution (Palou, McQuade, & Rossmann, ). In a contrasting manner, others (Chifor et al., ; Nguyen, Le, Kaipatur, & Major, ; Nguyen et al., ; Tsiolis, Needleman, & Griffiths, ) showed promising outcomes using higher frequency ultrasound that yield better image resolution. A recent proof‐of‐principle study (Chan, Wang, Fowlkes, Giannobile, & Kripfgans, ) showed that ultrasound can image important oral anatomical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advances have supported the exploration of additional strategies for caries detection with a particular emphasis on diagnosis at an earlier stage of formation without using ionizing radiation. A previous study, 13 assessed the effectiveness and reliability of a high resolution ultrasonography device by comparing its findings with those of clinically available radiographic techniques. 13 Similarly, in order to assess the validity and effectiveness of the innovative technique presented here, we compared THz imaging with common radiological techniques such as; intraoral periapical images and CBCT images.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study, 13 assessed the effectiveness and reliability of a high resolution ultrasonography device by comparing its findings with those of clinically available radiographic techniques. 13 Similarly, in order to assess the validity and effectiveness of the innovative technique presented here, we compared THz imaging with common radiological techniques such as; intraoral periapical images and CBCT images. The present study was designed to evaluate the imaging capacity of THz waves by using reflection measurements.…”
Section: Discussionmentioning
confidence: 99%